Microbial symbiosis in marine sponges: Overview on ecological aspects - Wilkesman Giamate, Jeff (Ciencia)
Sponge-microbe associations involve a diverse range of heterotrophic bacteria, cyanobacteria, facultative anaerobes, unicellular algae, and Archaea. Among the suggested benefits that these symbionts may provide to the sponge include nutrition through direct incorporation of dissolved organic matter in the seawater, nutrition through translocation of photosynthate from symbiotic cyanobacteria, transportation of metabolites through the sponge mesohyl, contribution to sponge structural rigidity, and assistance in chemical defense. The biology of the bacterium-sponge relationship has obtained considerable interest as a source of natural products. Sponges produce diverse and unusual bioactive compounds with a high potentiality for further development as drugs and research tools. However, sometimes the metabolite source is uncertain and determination of its origin is difficult, due basically to complications in microbial culture of symbionts. This overview resumes the state of the art of investigations about sponges and its symbionts.